Clinical profile of steroid-induced glaucoma in Bali Mandara Eye Hospital year 2019 - Ni Kompyang Rahayu; Ardelia Emily (DiscoverSys Inc., 2021)
Introduction: Glaucoma is an optic neuropathy characterized by optic disc cupping and visual field loss usually associated with raised intraocular pressure. Glaucoma incidence is rapidly increasing, with global incidence is estimated to reach 76 million in 2020. There are many causes of glaucoma; one of them is corticosteroid use. Unmonitored steroid use can be resulting in undesirable side effects such as steroid-induced glaucoma. This study aims to evaluate the clinical profile of steroid-induced glaucoma in Bali Mandara Hospital year 2019.Method: A descriptive-cross sectional study was conducted using secondary data involving 35 medical records of patients diagnosed with glaucoma in Bali Mandara Eye Hospital, Denpasar, from January to December 2019. Age, gender, steroid type, routes and duration of steroid administration were recorded from medical records. Obtained data were analyzed descriptively using SPSS version 23 for Windows. Results: Patient’s characteristics mostly were male 57.14% and 42.86% female, 31.43% were elderly >55 years old. They mostly used eye drops steroid (85.71%), and 14.29% took oral steroids. The most used eye drops were Dexamethasone eye drops (77.14%). For oral steroids, they took Methylprednisolone (8.57%) and Dexamethasone (5.71%). Most of them have symptoms after one year of steroid use (34.39%). Conclusion: Steroid-induced glaucoma can occur in both males or females in all age groups, which the elderly and children have a higher risk. Most cases occur from topical steroids. Steroid-induced glaucoma is avoidable irreversible blindness. Therefore, the use of steroids must be judicious; self-medication must be avoided. The doctor must provide education to patients who are given steroid therapy.